Implementasi Metode Fuzzy - Tsukamoto Untuk Diagnosis Penyakit Pada Kelamin Laki Laki - Yusuf Ferdiansyah; Nurul Hidayat (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Venereal disease is a disease that strikes in the genital organs of male or female which usually brings in through sex or oral sex. Venereal disease has long been scattered in several countries, one of them in Indonesia. Venereal disease has become so important that discussion after the AIDS disease cases arise which cause a large number of victims died. Venereal disease can be transmitted from one person to another through sexual contact. In Indonesia, the sexually transmitted disease that is most widely found is syphilis and premenstrual syndrome, the prevalence of sexually transmitted diseases in Indonesia is very high in Jakarta found prevalence of premenstrual syndrome 29.8% 25.2% and syphilis, chlamyd He was 22.7%. Tsukamoto Fuzzy method is a method that has a tolerance on the data and very flexible. The advantages of the method are namely Tsukamoto is intuitive and can give feedback based on information that is not accurate, qualitative, and ambiguous. On the methods of Tsukamoto, each Rule is represented by a set of Fuzzy membership functions with a monotonous called fuzzifikasi. As a result, output the result of each Rule in the form of value of the firm (crisp) based on Î±-predicate or the minimum value of each Rule and the value of z. end result is obtained by performing a weighted average defuzzifikasi. In this research the required variable is a list of symptoms and venereal disease in men is accompanied by a weighted. This research resulted in an average accuracy rate of 81.67% system.